Ritual e forma no coreocinema de Maya Deren - Machado, Nicole Donato Pinto (2024)
This research seeks to answer how Maya Deren's notion of ritual informed her theoretical and filmic work, and how it transformed itself throughout the development of her choreocinema, by identifying and analyzing ritualistic elements in her films. To establish the Derenian concept of ritual, we determined the theoretical concepts of the ritualistic art form. To analyze her films, we categorized her choreocinema into three phases. In the first phase, with the support of Turner and Schechner's Anthropology of Performance, Meshes of the Afternoon, At Land, A Study in Choreography for Camera and Ritual in Transfigured Time were analyzed from the perspective of the rite of passage. The second phase was dedicated to the documentary project about Haitian voodoo, due to the choreographic characteristics present in the existing film sequences, and to the book Divine Horsemen, resulting from this experience, in its description of the basic principles of such cosmology. The third phase, composed of Meditation on Violence and The Very Eye of Night, was analyzed based on the encounter between the cosmology of voodoo and the Derenian ritualistic form, in an update of her choreocinema. Finally, Deren's montage is put into dialogue with the montage logics presented by Vincent Amiel, and is highlighted for its relevance in Maya Deren's vertical cinema proposal, and in the construction of rhythm in the ritualistic form.